PRIMARY FACTORS CONTRIBUTING TO HOMELESSNESS IN INDUSTRIAL DIVISION OF MBALE CITY - AJOK BRENDA (My University, 2024)
ABSTRACT Homelessness is one of the most threatening challenges affecting both the global and national citizens. The complexity of homelessness, influenced by several primary factors, requires a multi-faceted approach to effectively address and mitigate its impact on individuals and communities industrial city division. This study sought to determine primary factors contributing to homelessness in Industrial City Division of Mbale City and it was guided by three to determine the various forms of homelessness in Industrial Division of Mbale City, to determine the factors that contributes to homelessness in Industrial Division of Mbale City and to determine interventions for preventing homelessness in Industrial Division of Mbale City. The study used qualitative case study design to analyze data from the study area with the help of both qualitative and quantitative methods. The researcher collected data from 15 respondents in the study area who were selected using simple random and purpose sampling and questionnaires together with interview guide were used to collect data. The study discovered that hidden homelessness is a common form of harmlessness. Other forms of homelessness found by the study included, transitional homelessness, episodic homelessness, chronic homelessness is also common. Findings also revealed that rent and eviction was found to contribute to homelessness. Other contributory actors found by the study included poverty, physical and mental health, human and natural disasters and discrimination findings show that provision of housing subsidies may help prevent homelessness. Further, study findings show that provision of night shelters for street sleepers and transitional housing is an intervention measure in preventing homelessness. Other interventions included provision of supportive and housing emergence services can help prevent homeless situations among the people. The study recommended that government and stakeholders should put in place measures of housing subsidies to improve peoples’ access to affordable but decent housing and government in conjunction with local leaders should sensitize the population about the dangers of homelessness and help build their capacities to own homes. Other recommendation included that government and stakeholders should provide temporary housing units to homeless people